Protective effect of Copaifera salikounda heckel against paracetamol-induced hepatorenal injury in rat - Aloke, Chinyere; Obasi, Nwogo Ajuka; Emelike, Chinedum Uche; Ogbu, Patience Nkemjika; Ufebe, Godswill Odumero; Orinya, Onyebuchi Federick; Ogbonnia, Egwu Chinedu; Onyekwere, Anthony Chinwendu (Penerbit Universiti Kebangsaan Malaysia, 2021)
Drug-induced hepatorenal damage is a significant worldwide clinical challenge. In Nigeria, Copaifera salikounda seed pod ethanol extract (CSSPEE) is used in the treatment of many ailments including liver disorders. This study investigated the protective efficacy of CSSPEE against paracetamol (PCM) induced hepatorenal toxicity. Male albino Wistar rats were assigned at random into five different groups (n = 6). The normal control (Group I) was given normal saline via oral administration while Group II was given 500 mg/kg body weight of PCM via intra-peritoneal administration; Group III was administered 100 mgkg-1 of silymarin (reference drug) while Groups IV and V were administered 200 and 400 mg kg-1 of CSSPEE, respectively, per os for seven days prior to administration of PCM. CSSPEE pretreated groups protected PCM-induced hepatorenal damage as reflected by significant diminution (P < 0.05) in liver enzymes activities and levels of malondialdehyde (MDA), total bilirubin (TB), triglycerides (TG) and urea in comparison with group II. Also, CSSPEE pretreatment significantly increased (P < 0.05) the activities of catalase and GSH relative to group II while no significant elevation (P > 0.05) in superoxide dismutase (SOD), glutathione peroxidase (GPx), and high-density lipoprotein (HDL) was observed in comparison to PCM group. CSSPEE also reversed liver and kidney PCM overdose caused histopathological alterations and ameliorated the tissue histology thereby corroborating the results of biochemical findings. CSSPEE produced analogous effects comparable to those produced by silymarin (reference drug). The results indicated that oral administration of CSSPEE conferred a dose-dependent protection against paracetamol-induced oxidative damage to liver and kidney